2022
DOI: 10.3389/fpubh.2022.937202
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness and use of 997 emergency medical service phone number during the COVID-19 pandemic

Abstract: BackgroundEmergency medical services (EMSs) are an important element of the healthcare system as it provides an opportunity to respond to critical medical conditions and save people's lives. In Saudi Arabia, EMS is offered via the EMS phone number “997” and mobile application “Asefny”.MethodsThis was an observational cross-sectional survey study exploring public awareness and use of the EMS phone number during the COVID-19 pandemic in Saudi Arabia. A bivariate analysis was performed to investigate factors affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Similar to the other studies, these results confirmed that EMS has been used by informed older adults more than those who were uninformed. [7][8][9]38 As demonstrated in previous literature, there was a high correlation between awareness and use of services, 8,9 and most often being uninformed about existing services was an obstacle to utilization of services. 7,38 Contrary to this study which showed a greater lack of awareness among women than among men, some previous studies have indicated that male caregivers were more likely to be unaware of the available services.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Similar to the other studies, these results confirmed that EMS has been used by informed older adults more than those who were uninformed. [7][8][9]38 As demonstrated in previous literature, there was a high correlation between awareness and use of services, 8,9 and most often being uninformed about existing services was an obstacle to utilization of services. 7,38 Contrary to this study which showed a greater lack of awareness among women than among men, some previous studies have indicated that male caregivers were more likely to be unaware of the available services.…”
Section: Discussionmentioning
confidence: 73%
“…7 The awareness and use of services were highly correlated. 8,9 The first meaning of service awareness is knowing that the intended services exist, but service awareness or lack of it is more complex than knowing that the intended services exist. Awareness is defined as being conscious of, having knowledge of, or being informed about it.…”
Section: Original Articlementioning
confidence: 99%
“…The probable reasons for these variations could be differences in urbanization, population density, level of communication, outreaches done in the area council, and historical emergency incidents in the area council. These factors have been noted as major drivers of awareness of emergency medical services in the literature [ 14 , 22 ]. The study also found a statistically significant difference in the level of awareness by gender.…”
Section: Discussionmentioning
confidence: 99%
“…The emergency care system indirectly impacts mortality and morbidity at all levels of society [ 12 , 13 ]. Hence, emergency care is essential to the health system as it is the first point of contact for many injured, including those in road crashes worldwide [ 7 , 14 ]. However, timely emergency care is not readily available or prohibitively expensive in some regions of the world [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shed light on the significance of public awareness concerning EMS and its implications for emergency response effectiveness. Studies conducted in Saudi Arabia and other developing countries have explored the extent to which the general population is informed about EMS services and their capabilities [ 6 8 ]. These investigations have consistently revealed a noticeable gap in public knowledge regarding EMS functions, availability, and how to access these critical services.…”
Section: Introductionmentioning
confidence: 99%